Assessment of psychological health effects of nurses during 2022–2023 of the COVID-19 pandemic: a descriptive study in Southern Taiwan - Hui-Ru Lin; Yung-Kuo Lee; Chen-Lin Chang; Ching-Hui Kuo; Hsin-Yun Ho; Chi-Jen Wu; Yi-Qian Chen; Cheng-Chun Wu; Yu-Cheng Ho; Tian-Huei Chu; Cheng-Hsin Chuang; Chou-Yuan Ko (Annals of Medicine)
Background Nurses on the frontlines of the pandemic have increased workloads, burnout, and virus exposure, leading to mental health challenges and a lack of resources for patient care. Mental health support for nurses during the COVID-19 outbreak has become a priority. This study evaluated psychological health outcomes of among nurses during the 2022–2023 COVID-19 pandemic in Taiwan, focusing on personal and work-related fatigue as key contributors to emotional distress.Methods A cross-sectional questionnaire was distributed to 200 nurses in a southern Taiwan hospital between 2022 and 2023. Emotional distress and mental health were assessed using the BSRS-5 (Brief Symptom Rating Scale) and CHQ-12 (Chinese Health Questionnaire). Correlation and regression analyses were conducted to identify factors influencing emotional distress and mental health outcomes.Results Nurses aged 40–59 (52.85, p = 0.01), those in emergency departments (56.71, p = 0.001), and those caring for COVID-19 patients (50, p = 0.007) reported higher personal exhaustion. Significant differences in work-related fatigue levels were observed based on working environments (52.78, p < 0.001), no beliefs regarding religion (46.53, p = 0.036), care for COVID-19 patients (47, p < 0.001) and previously diagnosed with COVID-19 (46.58, p = 0.005). Key factors influencing emotional distress included marital status, number of children, and workplace (p < 0.05), while mental health variations were noted  in age, marital status, number of children, workplace, and years of experience (p < 0.05). During the COVID-19 pandemic, nurses’ emotional distress and mental health were significantly correlated with specific stressors such as age, workplace, care for confirmed COVID-19 patients, and previous COVID-19 diagnoses (p < 0.001).Conclusions and implications for nursing management This study highlights the stressors affecting nurses’ mental health during the 2022–2023 COVID-19 pandemic, emphasizing the need for stress-specific mental health support. Understanding these stress-specific factors is important for figuring out what nurses need to improve their mental health, which can lead to better care for patients.